Morphine-induced conditioned place preference and the alterations of p-ERK, p-CREB and c-fos levels in hypothalamus and hippocampus: The effects of physical stress - Pahlevani, P.; Fatahi, Z.; Moradi, M.; Haghparast, A. (Cellular and Molecular Biology, 2014)
The hypothalamus and hippocampus are important areas involved in stress responses and reward processing. In addition, ERK/CREB pathway plays a critical role in the control of cellular responses to stress and reward. In the current study, effects of acute and subchronic stress on the alteration of p-ERK, p-CREB and c-fos levels in the hypothalamus and hippocampus of saline- or morphine-treated animals during morphine-induced conditioned place preference (CPP) procedure were investigated. Male Wistar rats were divided into two saline- and morphine-treated supergroups. Each supergroup includes of control, acute stress and subchronic stress groups. In all of groups, the CPP procedure was done, afterward the alternation of p-ERK/ERK ratio, p-CREB/CREB ratio and c-fos level in the hypothalamus and hippocampus were estimated by Western blot analysis. The results indicated that in saline- or morphine-treated animals, p-ERK/ERK ratio, p-CREB/CREB ratio and c-fos level increased after application of acute and subchronic stress (except for p-ERK/ERK ratio in morphine-control group). Our findings revealed that in saline- or morphine-treated animals, acute and subcronic stress increased the p-ERK/ERK ratio, p-CREB/CREB ratio and c-fos level in the hypothalamus and hippocampus and this enhancement in morphine-treated animals, was more considerable than that in saline-treated animals.